U-TH-PB AND SM-ND ISOTOPIC SYSTEMATICS OF THE GOALPARA UREILITE: RESOLUTION OF TERRESTRIAL CONTAMINATION - Tatsumoto M.; Torigoye-Kita N.; Misawa K. (My University, 1995)
The U-Th-Pb and Sm-Nd isotopic systematics of mineral separates from the Goalpara ureilite were studied after applying acid leaching techniques. The separates were successively leached with dilute HBr and HNO3 in order to remove any secondary Pb components in the meteorite as well as to separate a light REE-rich component which has been known to be dissolved using a similar acid leaching procedure. The leachates contained large amounts of terrestrial Pb as well as significant amounts of U, Th, Sm, and Nd, whereas the residues were highly depleted in all five of these elements (between 0.1 and 0.001 times CI chondritic abundance). The U-Pb, Th-Pb, and Sm-Nd isotopic systematics can be interpreted as mixtures of highly depleted ureilite and terrestrial contamination in all fractions. For this reason, precise ages could not be obtained from any of these systems. The lead isotopic compositions in the residues are considered mixtures of terrestrial Pb and primordial meteoritic Pb (Canon Diablo troilite Pb) with a small amount of radiogenic Pb. However, on a U-Pb concordia diagram the residues indicate a formation age as old as 4.55 Ga, assuming the U-Pb data represent a mixture of terrestrial and ureilite U and Pb. Similarly, Sm-Nd systematics of the residues form a mixing line between the composition of 4.55-Gy old material and an average terrestrial crustal composition, yielding a 3.74-Ga pseudo-isochron. Furthermore, the acid leachates show terrestrial signatures of ThU and SmNd ratios, and Pb and Nd isotopic ratios. Therefore, it is doubtful that the so-called light REE-rich component in ureilites is indigenous, and that the implied metasomatic event on the ureilite parent body is real.